Fingerprint of Exhaust Gases and Database of Microbial Diversity During Silkworm Excrement Composting. Issue 1 (2nd January 2018) - Li, Li; Liao, Sentai; Li, Weiming; Xing, Dongxu; Luo, Guoqing; Li, Qingrong; Ye, Mingqiang; Xiao, Yang; Yang, Qiong
ABSTRACT: Composting can convert silkworm excrement (SE) into good fertilizer, but the popularization of this practice is greatly hampered due to the strong odor produced. Determining the gas pollutants, the potential native aerogenic microorganisms and deodorant microorganism communities will lay foundations for developing good strategies to deal with malodor pollution from SE composting. This study qualitatively and quantitatively analyzed the exhaust gas and the microbial diversity. With a combination of solid-phase micro-extraction-gas chromatography tandem mass spectrometry technology and other methods of Chinese national standards, 43 odor pollutants from SE composting were identified and quantified. Ammonia, sulfur dioxide and hydrogen sulfide were the three major pollutants among the volatile inorganic compounds, with concentrations far exceeding the permissible standards for workplaces in China. 5-Ethyl-2, 2, 3-trimethyl-heptane, 2, 2, 4, 6, 6-5-methyl-heptane and 5-isobutyl-nonane accounted for 46.58% of volatile organic compounds. Using analysis of ribosome DNA sequences with Illumina Miseq PE 2 * 250, a next generation high-throughput sequencing technology, more than 694 bacteria (and actinomycetes) and more than 136 fungi were annotated, including groups of native aerogenic microorganisms and deodorant microorganisms. This study indicated a serious malodor problem and abundant microorganisms from SE composting and provided basic data not only for odor pollution control but also for future functional microorganism studies.